THU0436 Real-World Comparative Effectiveness of Adalimumab and Tocilizumab for the Treatment of Rheumatoid Arthritis: Results of an Administrative Claims Analysis. (9th June 2015) - Garg, V.; Griffith, J.; Hayes, O.A.; Bao, Y.
Abstract : Background: Previous meta-analyses suggest improved efficacy of ADA+MTX compared to TCZ+MTX, however, no comparison was made to TCZ monotherapy. 1 Objectives: To compare the real-world effectiveness of ADA+MTX vs TCZ in treating biologic-naïve RA patients. Methods: A retrospective (2005–2013), longitudinal cohort study was performed using a large US commercial administrative claims database. Biologic-naïve patients aged ≥18 years with a 1st diagnosis of RA and no diagnosis of spondyloarthritis, psoriasis, psoriatic arthritis, ulcerative colitis, or Crohn's disease within the study period were included. Patients who initiated ADA+MTX therapy were matched 1:1 with patients who initiated TCZ monotherapy, based on RA duration (±30 days) and date of biologic initiation (±360 days). Effective disease control over 1 year was defined using a validated algorithm that included the following elements: high adherence to the target biologic therapy (≥80% ADA adherence by medication possession ratio or receipt of 11–12 TCZ infusions), biologic dose escalation, switching to/adding a biologic or nonbiologic disease-modifying antirheumatic drug (nbDMARD), escalation of oral corticosteroid dose, or receipt of >1 glucocorticoid joint injection 2 . Effectiveness was compared after adjusting for the following covariates using multivariate logistic regression and Cox proportional hazard analyses: age, sex, Charlson Comorbidity Index, insurance type, geographic region, RA duration, number of prior DMARDs used, and number of rheumatologist visits between baseline and 1 year. Results: Mean age among 648 patients included (324 ADA+MTX; 324 TCZ) was 49.4 years; 18.1% were male. Baseline sociodemographic and clinical characteristics were similar between patient cohorts. At year 1, a significantly greater proportion of patients on ADA+MTX achieved effective disease control vs those on TCZ (29.6% vs 15.4%; P <0.001). Patients on ADA+MTX were less likely than those on TCZ to switch or add nbDMARDS (3.4% vs 10.8%; P <0.001), to escalate their biologic dose (17.0% vs 48.8%; P <0.001), or to have a 2nd corticosteroid injection (4.9% vs 11.4%; P =0.003). When controlling for baseline sociodemographic and clinical characteristics, patients on ADA+MTX were more likely than those on TCZ to be effectively treated (odds ratio=2.43, 95% CI=1.36 to 4.32). Compared to TCZ monotherapy, ADA+MTX treatment was associated with lower probability of switching or adding nbDMARDs, biologic dose escalation, or >1 corticosteroid joint injection (Table ). Conclusions: This study demonstrated real-world superiority of ADA+MTX therapy over TCZ monotherapy among RA patients. Future research to examine these findings in a randomized clinical trial may provide further evidence in this area. References: Liu Y et al. Adv Ther. 2012;29(7):620–34. Curtis JR et al. Arthritis Res Ther. 2011;13:R155. Disclosure of Interest: V. Garg Shareholder of: AbbVie, Employee of: AbbVie, J. Griffith Shareholder of: AbbVie, Employee of: AbbVie, O. Hayes Shareholder of: AbbVie, Employee of: AbbVie, Y. Bao Shareholder of: AbbVie, Employee of: AbbVie